Standardized cancer incidence disparities in Upper Manhattan New York City neighborhoods: the role of race/ethnicity, socioeconomic status, and known risk factors. Issue 4 (July 2016) - Hashim, Dana; Farhat, Zeinab; Wallenstein, Sylvan; Manczuk, Marta; Holcombe, Randall F.; Thorpe, Lorna; Schymura, Maria J.; Lucchini, Roberto G.; Boffetta, Paolo
Abstract : We examined the effects of race/ethnicity and neighborhood, a proxy of socioeconomic status, on cancer incidence in New York City neighborhoods: East Harlem (EH), Central Harlem (CH), and Upper East Side (UES). In this ecological study, Community Health Survey data (2002–2006) and New York State Cancer Registry incidence data (2007–2011) were stratified by sex, age, race/ethnicity, and neighborhood. Logistic regression models were fitted to each cancer incidence rate with race/ethnicity, neighborhood, and Community Health Survey-derived risk factors as predictor variables. Neighborhood was significantly associated with all cancers and 14 out of 25 major cancers. EH and CH residence conferred a higher risk of all cancers compared with UES (OR=1.34, 95% CI 1.07–1.68; and OR=1.39, 95% CI 1.12–1.72, respectively). The prevalence of diabetes and tobacco smoking were the largest contributors toward high cancer rates. Despite juxtaposition and similar proximity to medical centers, cancer incidence disparities persist among EH, CH, and UES neighborhoods. Targeted, neighborhood-specific outreach may aid in reducing cancer incidence rates. Abstract : Supplemental Digital Content is available in the text.